Vroomova teorija pričakovanja - motivacija za učenje v Sloveniji, Angliji in na Finskem - Lenar, Jurij (Šolsko polje, 2014)
In this article, I wanted to find out which variables among Vroom's expectancy theory have an effect on attitudes toward learning of school subjects. Besides that I also wanted to find out if there are some gender differences in this effect. For this purpose I analysed eighth grade students, who participated in TIMSS (Trends in International Mathematics and Science study) in 1999, 2003, 2007 and 2011. From TIMSS questionnaire for students, I used questions about students' engagement in learning, students' valuation of mathematics and science, educational expectations of students and students' confidence in mathematics and science. In the analysis, I included data from Slovenia, England and Finland. With the exception of educational expectations of students, I created composite variables (as average values of combined variables) which measure positive attitudes toward learning of school subjects, engagement in lessons of school subjects lessons,confidence in school subjects and valuation of school subjects. I used multiple regression to analyse data. With the t value, I wanted to find out if a certain variable has an effect on positive attitudes toward learning of school subjects. I discovered that I can in, all three countries, confirm Vroom's expectancy theory with most variables included in analysis. The results of the analyses have shown that students from all three countries have more positive attitudes toward learning of school subjects if they are engaged in lessons of school subjects, if they are confident in learning school subjects and if they value school subjects. In all cases except those of students from England in TIMSS 2007 and 2011, I can confirm Vroom's expectancy theory also with educational expectations of students.
Keywords: matematika; mathematics; naravoslovje; positive attitudes towards learning; motivacija; motivation; students; school subject; mednarodne raziskave; TIMSS; preverjanje znanja; učenci; osnovne šole